Interstitial pulmonary fibrosis in a Malaysian captive asian elephant (Elephas Maximus) - Y. Yakubu; Bee Lee Ong; M. M. Noordin; Z. Zakaria; K. Jayaseelan; R. S. K. Sharma; S. Sumita; M. Firdaus; Z. Kamarudin (2014)
A 14-year-old female captive Asian elephant in a Malaysian zoo with a history of positive sero-reactivity to Elephant TB